2004
DOI: 10.1104/pp.104.043141
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Transcript Accumulation during the Development of Dehydration Adaptation in Cicer arietinum  

Abstract: Cool season crops face intermittent drought. Exposure to drought and other abiotic stresses is known to increase tolerance of the plants against subsequent exposure to such stresses. Storage of environmental signals is also proposed. Preexposure to a dehydration shock improved adaptive response during subsequent dehydration treatment in a cool season crop chickpea (Cicer arietinum). We have identified 101 dehydration-inducible transcripts of chickpea by repetitive rounds of cDNA subtraction; differential DNA-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 63 publications
4
99
2
Order By: Relevance
“…Most of the clones showed significant sequence similarities to the genes previously identified as stress-responsive genes and senescence-related genes from other plant species. [36][37][38] RT-PCR confirmed increased expression of seven genes selected from the identified clones during manufacture (Fig. 3).…”
Section: Discussionmentioning
confidence: 92%
“…Most of the clones showed significant sequence similarities to the genes previously identified as stress-responsive genes and senescence-related genes from other plant species. [36][37][38] RT-PCR confirmed increased expression of seven genes selected from the identified clones during manufacture (Fig. 3).…”
Section: Discussionmentioning
confidence: 92%
“…Pre-soaking seed treatment with ABA was reported to significantly enhance the antioxidant enzymes activity in maize seedlings subjected to water stress (Jiang and Zhang 2002). Similarly, Boominathan et al (2004) found that relative water content of ABA treated plants was higher under drought stress. Moreover, exogenous application of ABA under water stress increased the grain weight in susceptible wheat cultivars (Nayyar and Walia 2004).…”
mentioning
confidence: 80%
“…ABA accumulation in vegetal tissues corresponds to metabolic and physiologic changes that occur during water stress in seedlings. The exogenous ABA application improves seedling adaptation after water stress (Boominathan et al 2004) and, when exogenously applied, leads to gene expression which respond to dehydration (Seki et al 2002, Wang et al 2002, Narusaka et al 2004.…”
Section: Discussionmentioning
confidence: 99%